Da palavra à imagem: o jogo mimético do brincar no conto “Teleco, o coelhinho”, de Murilo Rubião - Lazzarini, Maria Carolina Lins Reginato (2019)
The present study proposes to read and interpret Murilo Rubião's tale “Teleco, o coelhinho” (1965/2016), relying on the magical realism and in the game of nonsensuous similarity, aiming to identify the play in its mimetic capacity, having as main axis the character's metamorphosis that gives name to the story and (non)enchants the narrator. In order to broaden up the reading of the work in question, by associating it with nonfrequent perspectives in the critical fortune of the Brazilian author, the following theoretical contributions are listed: A literatura do maravilhoso (1987), by Alejo Carpentier, Karl Erik Schollhammer's essay “As imagens do realismo mágico” (2004), and O realismo maravilhoso (2017), by Irlermar Chiampi, to delineate the concept of magical realism and its variables; Walter Benjamin's essays “Doctrine of the Similar” (1933/2012), “Toys and Play” (1928/2012), and “The Cultural History of Toys” (1928/2012) support our reflection on the concept of production of nonsensuous similarities, being corroborated by the writings of Anita Helena Schlesener, “Mímesis e infância: observações acerca da educação a partir de Walter Benjamin” (2009), and Jeanne Marie Gagnebin's, “A criança no limiar do labirinto” (2013). From these studies, it is expected to understand the artistic procedures used in the construction of the character's metamorphosis as the essence of playing in Murilo Rubião's “Teleco, o coelhinho”, as well as to raise a collaborative discussion about playing as a possible narrative constituent to the tale